MXene Ti3C2Tx absorber for a 1.06 μm passively Q-switched ceramic laser - Feng, Xiao-Yue; Ding, Bao-Yong; Liang, Wei-Yuan; Zhang, Feng; Ning, Ting-Yin; Liu, Jie; Zhang, Han (Laser physics letters, 2018)
MXenes, a new family of two-dimensional materials, were prepared by a selective chemical etching method and the saturation absorption characteristics were measured using the Z-scan method. At 1.06 μm, a passively Q-switched Nd:YAG ceramic laser was operated by using MXene Ti3C2Tx as a saturable absorber successfully for the first time. At an absorbed pump power of 4.14 W, the pulse repetition rate was 186 kHz and the minimum pulse width was 359 ns. The maximal peak power and single-pulse energy were 2.04 W and 0.66 μJ respectively. This study demonstrates that MXenes show promise as saturable absorbers in laser technology.